Twin Peaks : unwrapping the plastic - Boulegue, Franck (Intellect, 2017)
Few contemporary television shows have been subjected to the critical scrutiny that has been brought to bear on David Lynch and Mark Frost's Twin Peaks since its debut in 1990. Yet the series, and the subsequent film, Fire Walk With Me, are sufficiently rich that it's always possible for a close analysis to offer something new - and that's what Franck Boulègue has done with Twin Peaks: Unwrapping the Plastic.